Endovascular Treatment of Acute Ischemic Stroke in Clinical Practice: Analysis of Workflow and Outcome in a Tertiary Care Center - Weissenborn, Karin; Gruber, Sam; Grosse, Gerrit M.; Gabriel, Maria; Schuppner, Ramona; Worthmann, Hans; Abu-Fares, Omar; Götz, Friedrich (Frontiers in Neurology, 2021)
Background and Purpose: Pre- and intra-hospital workflow in mechanical recanalization of large cervicocephalic arteries in patients with acute ischemic stroke still needs optimization. In this study, we analyze workflow and outcome in our routine care of stroke patients undergoing mechanical thrombectomy as precondition for such optimization. Methods: Processes of pre- and intra-hospital management, causes of treatment delay, imaging results (ASPECTS, localization of vessel occlusion), recanalization (mTICI score) and patient outcome (mRS at discharge and at the end of in-patient rehabilitation) were analyzed for all patients who underwent mechanical thrombectomy between April 1, 2016 and September 30, 2018 at our site. Results: Finally, data of 282 patients were considered of whom 150 (53%) had been referred from external hospitals. Recanalization success and patient outcome were similar to randomized controlled thrombectomy studies and registries. Delay in treatment occurred when medical treatment of a hypertensive crisis, epileptic fits, vomiting or agitation was mandatory, but also due to missing pre-notification of the hospital emergency staff by the rescue service, multiple mode or repeated brain imaging and transfer from another hospital. Even transfer from external hospitals located within a 10 km radius of our EVT center led to a median increase of the onset-to-groin-time of about 60 minutes. Conclusion: The analysis revealed several starting points for an improvement in the work-flow of thrombectomy in our center. Analyses of work-flow and treatment results should be carried out regularly, to identify potential for optimization of operational procedures and selection criteria for patients who could benefit from endovascular treatment.